La fritura de los alimentos : el aceite de fritura (2009)
ABSTRACT: The oil changes during deep-frying independent of kind. The change can be reduction of nutrients or formation of toxic component that through to food and then can be consumption. The transformation can be slow or fast depend of care during cooking, of parameter like as the control of temperature, kind of food, relation oil: food, equipment, addition of new oil as reposition, clean of oil and storage, something else. To know that the polar components and the monomer and polymers of cyclic acid fatty are the parameters internationals of quality and how can be identificated easy and quietly, it’s important because when an oil for deep-frying is no good it won’t be used and this way prevent risk for health of people like fried food.